2018
DOI: 10.4047/jap.2018.10.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of implant-supported monolithic crowns cemented to zirconia hybrid-abutments: zirconia-based crowns vs. lithium disilicate crowns

Abstract: PURPOSEThe aim of this in vitro study was to investigate the fracture resistance under chewing simulation of implant-supported posterior restorations (crowns cemented to hybrid-abutments) made of different all-ceramic materials.MATERIALS AND METHODSMonolithic zirconia (MZr) and monolithic lithium disilicate (MLD) crowns for mandibular first molar were fabricated using computer-aided design/computer-aided manufacturing technology and then cemented to zirconia hybrid-abutments (Ti-based). Each group was divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…According to Rohr et al [74], the use of resin cements with high compressive strength was found to be correlated linearly to fracture resistance and flexural strength of implant-supported monolithic zirconia crowns. Elshiyab et al [90] proved that after 5 years equivalent chewing simulation, implant retained monolithic zirconia crowns survived, although their resistance to fracture had decreased.…”
Section: Strength Of Monolithic Zirconiamentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rohr et al [74], the use of resin cements with high compressive strength was found to be correlated linearly to fracture resistance and flexural strength of implant-supported monolithic zirconia crowns. Elshiyab et al [90] proved that after 5 years equivalent chewing simulation, implant retained monolithic zirconia crowns survived, although their resistance to fracture had decreased.…”
Section: Strength Of Monolithic Zirconiamentioning
confidence: 99%
“…The highest resistance was observed for zirconia crowns. All specimens survived the mastication simulation.N/AThermal and mechanical cycling 5000 cycles, 5°-55 °C, waterMechanical loading 100 N, 12 × 10 5 cycles.Sarıkaya et al (2018) [87]- BruxzirFracture strength, crosshead speed 1 mm min −1 (crowns: force applied on buccal and lingual cusps, FPDs: force applied on occlusal connector area).- No fractures during chewing simulationN/A- Incoris TZIAging: thermocycling (10,000 cycles /5–55 °C / dwell time = 60 s / transfer time = 10 s,- Bruxzir crowns and FPDs presented significantly higher fracture strength compared to Incoris TZIDual axis chewing simulator with a total of 1,200,000 cycles.- No significant difference in fracture strength of crowns and FPDs fabricated from BruxzirWeigl et al (2018) [85]Zirkon BioStar HTFracture strength, crosshead speed 1 mm min −1 - All 0.5 mm crowns exceeded 900 N.N/AAging: chewing simulation (1,200,000 cycles, 50 N, f = 1.6 Hz))− 0.2 mm adhesively cemented control crowns exceeded 900 N.Thermal cycling (2 × 3000 between 5 °C and 55 °C, 2 minutes for each cycle)Elshiyab et al (2018) [90]-Zenostar ZrFracture strength, crosshead speed 1 mm min −1 - Monolithic lithium disilicate crowns presented lower fracture strength compared to monolithic zirconiaN/A- IPS e.max- CADAging: fatigue by chewing simulation with 1.2 million cycles + thermal cycling at 5–55 °C in distilled water (5118 thermal cycles with 60 s dwell time for each cycle, 15 s pause time).- All crowns presented a reduction in fracture strength following fatigue aging.Yin et al [89](2019)A3 12 T, Liaoning Upcera, Benxi, ChinaFracture strength, crosshead speed 1 mm min −1 After polishing the crown presented higher fracture strengths than after adjustment of occlusal contactNot calculated but observed in the diffraction patterns depending on the polishing methodDifferent polishing protocols were evaluated. Cementation using resin cement.Chewing simulation with cyclic loads between 2 and 300 N, frequency 1 Hz (100,000 cycles)Elsayed et al (2019) […”
Section: Strength Of Monolithic Zirconiamentioning
confidence: 99%
“…Thus, the hybrid abutment is developed by combining the Ti strength and the esthetic nature of ceramic materials (8). Drawing upon previous statements, the clinical success of the hybrid abutment depends on the cementation technique used to create a link between the ceramic and the metal (Ti).…”
Section: Introductionmentioning
confidence: 99%
“…The proposal of using an hybrid abutment is very interesting so that unitary crowns with a great ceramic volume would have similar aesthetic characteristics to the adjunctive teeth, which is not always possible with conventional abutments 5,6 . Hybrid abutment are suggested to present mechanical properties similar to titanium abutments 4,7,8 and promising durability and strength after long-term 9 .…”
Section: Introductionmentioning
confidence: 99%